Behcet”™s Disease and iga Nephropathy: Report of This Association in a Patient From Brazil And Literature Review - FCBC Fernandes, Paula; Silva Júnior, Geraldo B; AS Barros, Fernando; Sousa, Daniela C; M Franco, Luciano; MSV Patrocínio, Régia (Investigación Clínica, 2009)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Behcet”™s disease (BD) is associated with renal involvement in about one-third of the cases and a variety of renal lesions have been reported. A 27-year-old man presented a history of recurrent oral and genital ulcers, associated with pseudofoliculitis and arthritis in his left knee. The first laboratory tests revealed: urea = 53mg/dL, creatinine = 1.8mg/dL. The urinalysis showed leukocyturia. Initial treatment with ceftriaxone, thalidomide and prednisone was instituted. He became clinically stable, with normal renal function, but presenting hematuria and proteinuria. One year later the patient presented dark urine. The new laboratory tests showed urea = 58mg/dL, creatinine = 1.4mg/dL, and mild proteinuria (500-1000mg/24h). Two years later the proteinuria was 2230mg/day. The renal biopsy showed one glomerulus with severe glomerular sclerosis, mild tubular atrophy, mild interstitial fibrosis and thickening of arterial walls. Treatment with captopril was started to decrease proteinuria. Two years later, the patient presented creatinine = 1.7mg/dL and proteinuria = 2509mg/day. A new renal biopsy evidenced proliferative crescentic glomerulonephritis, with diffuse granullary deposits of IgA, IgM and C3. It was instituted pulsotherapy with metilprednisolone, monthly endovenous cyclophosphamide and maintenance prednisone. The patient became clinically stable, with creatinine of 1.3mg/dL and proteinuria of 500mg/day. BD could be one of the various causes of secondary IgA nephritis. It is important to periodically perform renal function evaluation in patients with BD, through urinalysis and measurement of serum creatinine and its clearance, in order to detect any abnormality and provide an early adequate treatment